UVCS/SOHO catalog of coronal mass ejections from 1996 to 2005: Spectroscopic proprieties. Issue 3 (28th March 2013) - Giordano, S.; Ciaravella, A.; Raymond, J.C.; Ko, Y.‐K.; Suleiman, R.
<x xml:space="preserve">Abstract</x> [1] Ultraviolet spectra of the extended solar corona have been routinely obtained by SOHO/UltraViolet Coronagraph Spectrometer (UVCS) since 1996. Sudden variations of spectral parameters are mainly due to the detection of coronal mass ejections (CMEs) crossing the instrumental slit. We present a catalog of CME ultraviolet spectra based upon a systematic search of events in the Large Angle and Spectrometric Coronagraph (LASCO) CME catalog, and we discuss their statistical properties. Our catalog includes 1059 events through the end of 2005, covering nearly a full solar cycle. It is available online at the URL http://solarweb.oato.inaf.it/UVCS_CME and embedded in the online LASCO CME catalog (http://cdaw.gsfc.nasa.gov/CME_list). The emission lines observed provide diagnostics of CME plasma parameters, such as the light‐of‐sight velocity, density, and temperature and allow to link the CME onset data to the extended corona white‐light images. The catalog indicates whether there are clear signatures of features such as shock waves, current sheets, O VI flares, helical motions, and which part of the CME structures (front, cavity, or prominence material) are detected. The most common detected structure is the cool prominence material (in about 70% of the events). For each event, the catalog also contains movies, images, plots, and information relevant to address detailed scientific investigations. The number of events detected in UV is about one tenth of the LASCO CMEs and about one fourth of the halo events. We find that UVCS tends to detect faster, more massive, and energetic CME than LASCO, and for about 40% of the events, it has been possible to determine the plasma light‐of‐sight velocity.